Moonlighting Proteins and Their Role in the Control of Signaling Microenvironments, as Exemplified by cGMP and Phytosulfokine Receptor 1 (PSKR1) - Irving, Helen R.; Cahill, David M.; Gehring, Chris (Frontiers in Plant Science, 2018)
Signal generating and processing complexes and changes in concentrations of messenger molecules such as calcium ions and cyclic nucleotides develop gradients that have critical roles in relaying messages within cells. Cytoplasmic contents are densely packed, and in plant cells this is compounded by the restricted cytoplasmic space. To function in such crowded spaces, scaffold proteins have evolved to keep key enzymes in the correct place to ensure ordered spatial and temporal and stimulus-specific message generation. Hence, throughout the cytoplasm there are gradients of messenger molecules that influence signalling processes. However, it is only recently becoming apparent that specific complexes involving receptor molecules can generate multiple signal gradients and enriched microenvironments around the cytoplasmic domains of the receptor that regulate downstream signalling. Such gradients or signal circuits can involve moonlighting proteins, so called because they can enable fine-tune signal cascades via cryptic additional functions that are just being defined. This perspective focuses on how enigmatic activity of moonlighting proteins potentially contributes to regional intracellular microenvironments. For instance, the proteins associated with moonlighting proteins that generate cyclic nucleotides may be regulated by cyclic nucleotide binding directly or indirectly. In this perspective, we discuss how generation of cyclic nucleotide-enriched microenvironments can promote and regulate signalling events. As an example, we use the phytosulfokine receptor (PSKR1), discuss the function of its domains and their mutual interactions and argue that this complex architecture and function enhances tuning of signals in microenvironments.